1984
DOI: 10.1093/carcin/5.8.993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, localization and regulation of a novel phenobarbital-inducible form of cytochrome P450, compared with three further P450-isoenzymes, NADPH P450-reductase, glutathione transferases and microsomal epoxide hydrolase

Abstract: Two cytochromes P450 (PB1 and PB2) have been isolated from the livers of rats treated with phenobarbital. PB2 (mol. wt. 53 500) is novel and is the first example of a phenobarbital-inducible enzyme with a Soret peak at 447 nm. Using an enzyme-linked immunosorbent assay, some immunochemical and structural similarities were observed between these cytochromes. PB1 and PB2 were induced by phenobarbital, Aroclor 1254, trans-stilbene oxide and to a lesser extent by isosafrole. Immunohistochemical localization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(70 citation statements)
references
References 35 publications
(31 reference statements)
7
61
1
1
Order By: Relevance
“…PB2b (PB21) on the basis of yield from the purification, appears to be present in rat microsomal fractions in low concentration. From previous studies PB2, was shown to be phenobarbital-inducible and highly localized in the centrilobular region of the liver [12], in contrast with the PB1 proteins, which are more diffusely distributed in this area [12]. We have also shown that both PB1-and PB2-related proteins are expressed in significant concentrations in human liver, but differences in the level of expression are observed between individuals.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…PB2b (PB21) on the basis of yield from the purification, appears to be present in rat microsomal fractions in low concentration. From previous studies PB2, was shown to be phenobarbital-inducible and highly localized in the centrilobular region of the liver [12], in contrast with the PB1 proteins, which are more diffusely distributed in this area [12]. We have also shown that both PB1-and PB2-related proteins are expressed in significant concentrations in human liver, but differences in the level of expression are observed between individuals.…”
Section: Discussionsupporting
confidence: 49%
“…In a previous report [12] we have described the isolation of two distinguishable forms of rat liver cytochrome P-450 (PB1 and PB2), which are only marginally induced by phenobarbital relative to certain other forms, namely PB35 and PB3b [5,6,8]. We have now isolated a series of proteins that appear structurally related to PB1 and PB2.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[6][7][8] Indeed, a significant body of evidence has been presented showing that the anatomical distributions of xenobiotic-metabolizing enzymes within tissues can greatly influence the cell specificity of chemically induced toxicities resulting from the biotransformation of relatively inert xenobiotics into electrophilically reactive metabolites. 6,7,9,10 While the localizations, distributions, and inductions of various phase I and phase II xenobiotic-metabolizing enzymes within parenchymal cells (i.e., hepatocytes) throughout the liver have received considerable attention during the past two decades, [6][7][8][9][11][12][13][14] little is currently known regarding the presence and inducibility of xenobiotic-metabolizing enzymes, particularly phase I enzymes, within intrahepatic biliary epithelial cells and other nonparenchymal liver cells. [15][16][17] Intrahepatic biliary epithelial cells have recently received considerable attention because of their ability to proliferate under certain pathophysiological conditions and because of the possibility that they might serve as the progenitor cell in the liver.…”
mentioning
confidence: 99%